2020
DOI: 10.1186/s12951-019-0570-3
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the angiogenic effects of nanomaterials: mechanisms involved and potential applications

Abstract: The vascular system, which transports oxygen and nutrients, plays an important role in wound healing, cardiovascular disease treatment and bone tissue engineering. Angiogenesis is a complex and delicate regulatory process. Vascular cells, the extracellular matrix (ECM) and angiogenic factors are indispensable in the promotion of lumen formation and vascular maturation to support blood flow. However, the addition of growth factors or proteins involved in proangiogenic effects is not effective for regulating ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 164 publications
(215 reference statements)
0
36
0
Order By: Relevance
“…It could release silicon ions and upregulate the expression of genes associated with angiogenesis and new tissue formation - [ 100] Hydrogel based on fayalite and NOCS…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…It could release silicon ions and upregulate the expression of genes associated with angiogenesis and new tissue formation - [ 100] Hydrogel based on fayalite and NOCS…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…In this study, it was reported that the CNTs have high sensitivity towards RSV through non bonded interactions which makes them a suitable drug carrier for safe and controlled release of RSV [ 97 ]. CNTs are also reported as carriers to deliver angiogenic factors to the ischemic tissues to promote angiogenesis [ 100 , 101 ].…”
Section: Application Of Cnms In Cardiovascular Tissue Engineeringmentioning
confidence: 99%
“…HA is widely used because it contains similar physical and chemical components to those of natural HA present in bone tissue [2]. Moreover, studies reported that HA induced a favorable immune response [7], exerted an angiogenic effect on defective bone tissue [8,9], and activated osteoblasts and osteoclasts for bone tissue remodeling by accelerating the differentiation of these cells [10,11].…”
Section: Introductionmentioning
confidence: 99%